Penggunaan Bahasa Indonesia dalam Pelayanan dan Promosi di AP Studio - Agustin, Puspita Dian; Ibrahim, Shintia Humairah Putri; Dukalang, Salsabillah; Putra, Bintang Akbar Dwi; Pujiarti, Tita; Lestari, Inggik Ayu; Alhasni, Hafizha; Tasalissa, Putri Diana; Sirupa, Stefanie Angelina; Dundo, Marsyah Azahra; Pantu, Amel; Arifin, Alfadina Intan; Saleh, Siti Lutfiyyah H.; Maharani, Fatimah Puan; Halid, Moh. Fadly (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the use of the Indonesian language in economic activities at AP Studio as a photography service business, particularly in the contexts of service delivery and promotion. This research employed a qualitative approach using a descriptive method, with data collected through observation, interviews with the owner and management of AP Studio, and documentation of promotional materials and social media content. The data were analyzed qualitatively through categorization, interpretation, and conclusion drawing. The findings indicate that the Indonesian language is dominantly used in promotional activities and the delivery of service information, such as explaining service packages, pricing, and booking procedures, while direct service interactions apply flexible communication by combining the Indonesian language with the local Gorontalo dialect to create a more comfortable and friendly service atmosphere. Adjusting language use according to context and customer characteristics enhances service efficiency, reduces potential misunderstandings, and strengthens interactions between service providers and customers. Overall, the communicative and contextual use of the Indonesian language contributes to improved customer comfort, supports operational effectiveness, strengthens AP Studio’s identity as a professional and approachable photography service business, and promotes business sustainability within the creative economy sector.